Goods Inventory Application at Sal Laptop Store Using Visual Basic.Net - Ardhi Pratomo; Leni Natalia Zulita; Lena Elfianty (Penerbit Jurnal Indonesia, 2021)
Stock data processing at Sal Laptop Store is still done manually, namely by using books, as a result, processing the data takes a long time. In fact, to process data items required an accuracy. Documentation of goods data in a company or business entity is very important. With the increasing number of incoming and outgoing goods data in a company/business entity, it is necessary to computerize data recording. The inventory application at Sal Laptop Store is an application that can be used to assist the store in managing goods data, sales and purchases of goods, besides that there are also outputs that can be used to find out sales and inventory reports at the store. The goods inventory application at the store is made using the Visual Basic .Net programming language and SQL Server database. Based on the results of system testing, it can be concluded that the functionality of the goods inventory application at Sal Laptop Store has been running well. Based on the results of system testing at the store, the application is appropriate and can help data processing, namely data on goods, purchases, and sales of goods, and the output provided can help control inventory and sales of goods.